Géohistoire du massif forestier d’Écouves (Orne, Normandie) - Nicolas Blanchard; Damase Mouralis; Dominique Todisco (Projets de Paysage)
Situated at the limits of the Armorican Massif and the Paris Basin, the Écouves Forest, due to its topography, its diachronic evolution and its special bio-pedological characteristics, differs from the corpus of forests found on plains and plateaus studied in recent years in metropolitan France. The geohistorical study of the Écouves Forest Massif is based on a multidisciplinary approach using methods employed in the fields of history (archive analysis), archaeology (prospecting on foot), archaeobotany (palynology, carbon-14 dating) and geography (the interpretation of maps and the integration of information generated by GISs). This article proposes an initial outline of the evolution of the Écouves Forest landscape over the last five centuries illustrating the construction of space (silvicultural dynamics, the transmission of forms) over a long period. Although the traces of anthropization appear to be more tenuous than elsewhere, this work stresses the need to understand the forest as a spatial palimpsest preserving superimposed anthropic legacies and bio-geographic dynamics which are of scientific interest.